Effect of O\(_2\) into N\(_2\) Afterglows in RF and Corona Discharges - André Ricard; Anne-Marie Pointu; Soo-Ghee Oh (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The afterglows in N2-O2 gas mixtures have been previously described: N - atoms titration by NO[A-1], oxygen in impurity in N2 at reduced gas pressure and at atmospheric gas pressure. The and O-atoms density versus the O2 percent from 1 to 4% into N2 in HF flowing afterglow (at 7 Torr, 0.5 slpm, 150w) was strongly decreasing for N-atoms from 15 to 21014cm-3 and kept a nearly constant value for O-atoms density: 7-9 1014cm-3, a value which is higher than the N-atom density in the range 2 - 10% O2 into N2. In RF afterglows, it was studied the effect of O-atoms and O2 molecules when O2 was introduced into N2 before or after the plasma (8 Torr, 1 slpm, 100 W ). It is concluded that a quenching of N2 active species by O-atoms more effective than with O2 in the early and late afterglows. At N2 the atmospheric gas pressure of Corona Plasmas with O2 impurity, it has been measured the density of the N2O1S excimer equal to about 1012cm-3, largely less than the N and N2 (A) densities: (5-7) 1014cm-3 .